LAJU RESAPAN BIOPORI PADA BEBERAPA TIPE TANAH BIOPORIAL APPROACHRATE IN VARIOUS SOIL TYPES - Lidia Anike Pandeirot; Josephus I Kalangi; Alfonsius Thomas (Universitas Sam Ratulangi, 2018)
ABSTACT Â The city of Manado annually experiences flooding in certain areas caused by changes in land use, a cycle of reduction in river capacity, and public awareness in disposing of garbage and maintaining a very low environment. The study was conducted at four locations namely Pandu subdistrict,Rurukan sub-district,Kali village and Matungkas village. In order to determine the rate of water absorption and the minimum amount of biopore infiltration holes in four different soil types. From this research, it is expected to be able to provide information for the government and the developing community to be taken into consideration in efforts to prevent flooding and minimize surface runoff. The method in this study uses a factorial randomized design as a method of retrieving data which is then analyzed using an analysis of two way variants. The results of the study show that the rate of recharge has a significant effect on the level of depth, and type of soil. The highest absorption rate is in the regosol soil type and at a depth of 75 cm. Keywords : Biopori, Floods, Biopore Infiltration Holes